Analysis of Service Science-Based Academic Service Development in the Management Study Program of UPN "Veteran" East Java - Priyambudi, Nico Akbar; Handayani, Wiwik Handayani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
In this era of digitalization, service science plays a vital role as a support for the successful implementation of the tri dharma of higher education in education, this can be done by developing innovations in terms of e-service quality using chatbots. The purpose of this research is to develop academic services for the UPN "Veteran" East Java Management undergraduate program through e-service quality innovation using chatbots. To determine satisfaction, measurements use the attributes of e-service quality, chatbot, and satisfaction. This research method uses descriptive quantitative through the measurements used are Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). The sample in this study used was non-probability with a purposive sampling method. The results obtained in this study indicate that the level of student satisfaction is at a value of 76% which is included in the satisfied criteria. Of the 13 attributes used, only 2 attributes are in accordance with student expectations, namely the attributes of natural language understanding and willingness to recommend.